Conservation manager's perceptions regarding biodiversity in the North-West Parks and Tourism Board - Van Jaarsveld, A.S. (University of Pretoria, 2013)
Dissertation (M Inst Agrar ( Sustainable Ecological Management))--University of Pretoria, 2007.